Recognition versus Disclosure of Future Loss Conditions and the Decision-Usefulness of Financial Statements - Kunz, Alexis H.; Staehle, Martin (The Accounting Review, 2020)
ABSTRACT We conduct an experiment to investigate the differential effect of recognizing versus disclosing reasonable and supportable forecasts of future loss conditions on investors' valuation assessments when economic fundamentals either deteriorate or improve. Our main finding is that when entities enjoy growth at constant risk, the accelerated recognition of future loss conditions can induce valuation assessments that are opposed to the entity's enhanced valuation. Supplementary analyses reveal that investors misattribute (some) expected losses to the entity's past performance and rely on unadjusted current summary earnings to assess the entity's prospects. Our findings provide insight into the cognitive processes that lead investors to incorrectly assess earnings trends and inform regulators, standard setters, investors, and preparers that the accelerated recognition of relevant and unbiased forward-looking loss estimates can impair the decision-usefulness of financial statements.